Does the Mediterranean diet reduce the odds of diabetic nephropathy in women? A case–control study - Noori, Sahar; Mirzababaei, Atieh; Abaj, Faezeh; Ghaffarian-Ensaf, Rasool; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Background: In recent decades, the prevalence of chronic diseases such as diabetes is increasing. One of the major complications of diabetes is diabetic nephropathy (DN), so it is important to find a way that can delay or control the onset of DN. Therefore, in this study, we investigated the relationship between the Mediterranean diet (MED) and the odds of DN. Methods: This case-control study was performed among 210 women (30-65 years) who were referred to the Kowsar Diabetes Clinic in Semnan, Iran. Biochemical variables and anthropometric measurements were assessed. Food frequency questionnaire (FFQ) was used to calculate dietary intakes. Data from dietary intakes based on FFQ was used to evaluate the MED score. Logistic regression was used to examine the associations. Result: Our results showed that in the crude model with higher adherence to the MED diet (OR: 0.272; 95% CI: 0.154, 0.481; P=0.001) odds of DN has reduced by 73%, and in the model1, after controlling for potential confounders, with higher adherence to MED diet (OR:0.239; 95% CI: 0.128, 0.447; P=0.001) odds DN has reduced by 76% compared to low adherence. Also, in model1, significant associations were observed between high consumption of grains (OR:0.360; 95% CI: 0.191, 0.676; P=0.001), legumes (OR:0.156; 95% CI: 0.083, 0.292; P=0.001), vegetables (OR:0.273; 95% CI: 0.149, 0.501; P=0.001), fruits (OR:0.179; 95% CI: 0.093, 0.347; P=0.001), fish (OR:0.459; 95% CI:0.254, 0.827; P=0.01) and reduced odds of DN (P ˂ 0.05). Conclusion: we observed that with higher adherence to the MED diet odds of DN had reduced through mechanisms. However additional studies are needed to confirm these findings.